How to Develop A Framework for the Investment of Temporary Government Cash Surpluses - Fainboim Yaker, Israel (IMF How To Notes; How-To Note ;, 2020)
Well-developed cash management aims to improve government operational efficiency and facilitates better service delivery by ensuring liquidity to meet payment obligations as they fall due. Liquidity, however, comes at a cost. Governments can reduce the cost of maintaining liquidity by proactively managing their cash balance at an appropriate level and prudently investing any excess liquidity. This note discusses the policy framework and processes that governments should put in place to identify, guide, and govern the investment of their surplus cash resources.